Pengaruh Insentif Terhadap Kinerja Karyawan di Kantor POS Regional X Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the effect of incentives on employee performance. This study was conducted at Regional X Makassar Post Office. The number of samples in this study were 56 employees in the Regional X Makassar Post Office. Data analysis was performed with a simple linear regression analysis. It was regression equation that described and explained the effect of one independent variable on the dependent variable, where the relationship could be described as a straight line. The results of this study showed that there was a strong relationship between incentives and employee performance of 0.888.  The influence of the independent variable or incentive (X) on the dependent variable of employee performance (Y), it was indicated by the Adjusted R Square value of 0.789, which meant 78.9% of the influence of the independent variable or incentive on the independent variable or employee performance at Makassar Regional X Post Office, from the output results were at a good level.